Optimal allocation for combined heat and power system with respect to maximum allowable capacity for reduced losses and improved voltage profile and reliability of microgrids considering loading condition - Naderipour A.; Abdul-Malek Z.; Nowdeh S.A.; Ramachandaramurthy V.K.; Kalam A.; Guerrero J.M. (Elsevier Ltd, 2023)
Genetic algorithms; Microgrids; Particle swarm optimization (PSO); Power generation; Reliability; Combined heat and power; Loss reduction; Maximum allowable; Micro grid; Voltage profile; Electric load loss; combined heat and power; energy planning; numerical method; optimization; power plant; reduction; standard (reference)